0
$\begingroup$

Let $X$ and $Y$ be independent random Poisson variables, both with parameter $\lambda$. Is there a simple closed form expression for $P(X \leq Y)$?

I know from this question that we have to evaluate something like the sum $$\sum_{\substack{0 \leq x, y \\ x \leq y}} \frac{\lambda^{x + y}}{x!y!},$$ but how is that done?

$\endgroup$
1
$\begingroup$

You assume equal means. We have

  • $1= P(X < Y) + P(Y<X) + P(Y=X)$
  • $P(Y<X) = P(X<Y) =q$
  • With $p=P(Y=X) \Rightarrow q =\frac{1-p}{2} \Rightarrow P(X\leq Y)=\frac{1-p}{2} + p =\frac{1}{2}(1+p)$
  • $p = P(X=Y) =e^{-2\lambda} \sum_{n=0}^{\infty} \frac{\lambda^{2n}}{(n!)^2} = e^{-2\lambda}I_0(2\lambda)$ $$\Rightarrow P(X\leq Y) = \frac{1}{2}(1+p) = \frac{1}{2}(1+e^{-2\lambda}I_0(2\lambda))$$
$\endgroup$
  • $\begingroup$ This is much simpler! I was hoping that someone had a better way to derive it. $\endgroup$ – rwbogl May 17 '18 at 15:48
1
$\begingroup$

If you accept special functions as closed forms, then the answer is $$P(X \leq Y) = \frac{1}{2} (1 + e^{-2\lambda} I_0(2\lambda)),$$ where $I_0$ is a modified Bessel function of the first kind. To derive this directly, read on.

The probability can be evaluated as the following sum: \begin{equation*} P(X \leq Y) = \sum_{\substack{0 \leq x, y \\ x \leq y}} \frac{\lambda^x}{x!} e^{-\lambda} \frac{\lambda^y}{y!} e^{-\lambda} = e^{-2\lambda} \sum_{\substack{0 \leq x, y \\ x \leq y}} \frac{\lambda^{x + y}}{x! y!}. \end{equation*} Ignore the $e^{-2\lambda}$ factor for a moment. This sum is symmetric in the sense that swapping summation variables does not change the terms. That is, $\lambda^{x + y}/ x!y! = \lambda^{y + x} / y!x!$. This lets us exploit the Iverson bracket identity $$[0 \leq x \leq y] + [0 \leq y \leq x] = [0 \leq x, y] + [0 \leq x = y].$$ Multiplying by our term and summing over all integers $x$ and $y$ yields \begin{equation*} \sum_{\substack{x, y \\ 0 \leq x \leq y}} \frac{\lambda^{x + y}}{x!y!} + \sum_{\substack{x, y \\ 0 \leq y \leq x}} \frac{\lambda^{x + y}}{x!y!} = \sum_{0 \leq x, y} \frac{\lambda^{x + y}}{x!y!} + \sum_{0 \leq x} \frac{\lambda^{2x}}{(x!)^2}. \end{equation*} Since our sum is symmetric, the two sums on the left are equal. On the right side, the first sum immediately factors as $(\sum_{x \geq 0} \lambda^x / x!)(\sum_{y \geq 0} \lambda^y / y!) = e^{2\lambda}$. The second sum can be seen to be $I_0(2\lambda)$, where $I_0(t)$ is defined as $$I_0(t) = \sum_{k = 0}^\infty \frac{\left(\frac{1}{4} t^2\right)^k}{(k!)^2}.$$ All together, this implies \begin{equation*} 2\sum_{\substack{x, y \\ 0 \leq x \leq y}} \frac{\lambda^{x + y}}{x!y!} = e^{2\lambda} + I_0(2\lambda). \end{equation*} Trivial manipulation then gives $$P(X \leq Y) = \frac{1}{2}(1 + e^{-2\lambda} I_0(2\lambda)),$$ as we claimed.


This can be "checked" by simulating the event. For $\lambda = 10$, our predicted probability is $(1 + e^{-20} I_0(20))/2 \approx 0.54489$. Using this code, one simulation generated $10^5$ $(X, Y)$ pairs of Poisson random variables of mean $10$. The actual proportion of pairs with $X \leq Y$ was $0.54598$, not too far from what we expected.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.